Forecasting Algorithm Based on Temperature Error Prediction Using Kalman Filter for Management System Development - Bogdanovs, N; Belinskis, R; Bistrovs, V; Petersons, E; Ipatovs, A (Latvian journal of physics and technical sciences, 2021)
The study offers a new method of collection and processing of meteorological data from the meteorological service based on observations and correction of numerical weather forecast errors using a new prediction algorithm. This algorithm vastly increases the accuracy of the short-term forecast of outdoor air temperature, which is subject to uncertainty due to the stochastic nature of atmospheric processes. Processing of temperature data using Kalman filter provides the decrease in predicted temperature errors. The main setup methods of Kalman filter have been examined. The article also describes the implementation of accuracy improving algorithm of predicted temperature using Python.